Model Sistem Informasi Absensi dan Mutasi Karyawan Pada PT ABCX Berbasis Web - Claresta Visakha; Iis Pradesan (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2023)
PT ABCX has several problems related to its personnel information system, including the absence of an attendance system for employees who work outside the office so that it becomes difficult to control the employee's attendance, then for employees who work in the office and take attendance with a fingerprint machine there is no related automatic recording system so that absenteeism is calculated manually from excel, and there is no system for recording and recording employee mutations. The development process is carried out using the Rational Unified Process (RUP) method and the method for analyzing problems uses use case diagrams and Entity Relationship Diagrams (ERD) while at the design stage the authors use Class Diagrams and Activity Diagram. System development uses Visual Studio Code and MySQL as database. The result of this research is the creation of an attendance system for employees who are outside the office, a system that is able to automatically calculate employee attendance from the fingerprint machine, as well as a system that is able to realize the recording and recording of employee mutations.Keywords: Absence; Mutation; Rational Unified Process; Visual Studio Code; MYSQL AbstrakPT ABCX memiliki beberapa permasalahan terkait sistem informasi kepegawaiannya antara lain belum adanya sistem absensi bagi karyawan yang berkerja diluar kantor sehingga menjadi sulit untuk mengontrol presensi karyawan tersebut, lalu untuk karyawan yang bekerja didalam kantor dan melakukan absensi dengan mesin fingerprint belum ada sistem perekapan otomatis terkait sehingga absensi dihitung manual dari excel, serta belum adanya sistem pencatatan dan perekapan mutasi karyawan. Proses pengembangan dilakukan dengan metode Rational Unified Process (RUP) dan metode untuk menganalisis permasalahan menggunakan usecase diagram dan Entity Relationship Diagram (ERD) sedangkan pada tahap perancangan penulis menggunakan Class Diagram dan Activity Diagram. Pengembangan sistem menggunakan Visual Studio Code dan MySQL sebagai basis data. Hasil dari penelitian ini ialah terciptanya sistem absensi untuk karyawan yang berada diluar kantor, sistem yang mampu menghitung presensi karyawan dari mesin fingerprint secara otomatis, serta sistem yang mampu mewujudkan pencatatan dan perekapan mutasi karyawan.